PENGARUH CORPORATE SOCIAL RESPONSIBILITY, UKURAN PERUSAHAAN DAN PERTUMBUHAN LABA TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur di Bursa Efek Indonesia Tahun 2017-2019) - Umi Lathifatu Nur Tri Mukti; Maslichah Maslichah; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The purpose of this research to determine the effect of corporate social responsibility on firm value, 2) To determine the effect of firm size on firm value and 3) To determine the effect of profit growth on firm value. Using sample of Manufacturing industry listed on the Indonesia Stock Exchange and research period of 2017-2019, the results show that in general there is an influence between Corporate Social Responsibility, company size and profit growth on firm value. This research is an quantitative research and the sample used by the researchers using purposive sampling technique. The technique used by the researcher is Multiple Linear Regression Analysis with the help of SPSS 21. Based on the hypothesis testing and analysis of the variables of corporate social responsibility, firm size and profit growth on firm value that have been described, it can be concluded as follows : 1.) The results of testing the corporate social responsibility variable have a positive and significant effect on firm value, 2.) The test results of the firm size variable have a positive and significant effect on firm value and 3.) The results of testing the profit growth variable have no effect on firm value.Keywords: Corporate Social Responsibility, Company Size, Profit Growth and Company Value.